Countdown to 2015: tracking donor assistance to maternal, newborn, and child health. - Powell-Jackson, T; Borghi, J; Mueller, D; Patouillard, E; Mills, A (2006)
BACKGROUND: Timely reliable data on aid flows to maternal, newborn, and child health are essential for assessing the adequacy of current levels of funding, and to promote accountability among donors for attainment of the Millennium Development Goals (MDGs) for child and maternal health. We provide global estimates of official development assistance (ODA) to maternal, newborn, and child health in 2003 and 2004, drawing on data reported by high-income donor countries and aid agencies to the Organisation for Economic Development and Cooperation. METHODS: ODA was tracked on a project-by-project basis to 150 developing countries. We applied a standard definition of maternal, newborn, and child health across donors, and included not only funds specific to these areas, but also integrated health funds and disease-specific funds allocated on a proportional distribution basis, using appropriate factors. FINDINGS: Donor spending on activities related to maternal, newborn, and child health was estimated to be US1990 million dollars in 2004, representing just 2% of gross aid disbursements to developing countries. The 60 priority low-income countries that account for most child and newborn deaths received 1363 million dollars, or 3.1 dollars per child. Across recipient countries, there is a positive association between mortality and ODA per head, although at any given rate of mortality for children aged younger than 5 years or maternal mortality, there is significant variation in the amount of ODA per person received by developing countries. INTERPRETATION: The current level of ODA to maternal, newborn, and child health is inadequate to provide more than a small portion of the total resources needed to reach the MDGs for child and maternal health. If commitments are to be honoured, global aid flows will need to increase sharply during the next 5 years. The challenge will be to ensure a sufficient share of these new funds is channelled effectively towards the scaling up of key maternal, newborn, and child health interventions in high priority countries.